2005
DOI: 10.1186/cc3028
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: An increasing number of diagnostic imaging procedures requires the use of intravenous radiographic contrast agents, which has led to a parallel increase in the incidence of contrast-induced nephropathy. Risk factors for development of contrast-induced nephropathy include pre-existing renal dysfunction (especially diabetic nephropathy and multiple myeloma-associated nephropathy), dehydration, congestive heart failure and use of concurrent nephrotoxic medication (including aminoglycosides and amphotericin B). Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…direct application of vasodilators such as dopamine, ANP or ET1 antagonists, failed to exert appreciable renoprotective effects [23], thus calling for the search of alternative ways to ameliorate CIN. In a number of studies, augmentation of adenosine formation, and consequent excretion in urine evident after the CM administration, has been implicated in inducing sustained vasoconstriction of afferent arterioles and vasodilation of efferent arterioles, thus reducing renal glomerular filtration rate and developing renal ischemia [24,25,26,27]. Studies involving theophylline, a direct selective renal adenosine antagonist, demonstrated controversial results with respect to the renoprotective vasodilatory properties of the latter [25,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…direct application of vasodilators such as dopamine, ANP or ET1 antagonists, failed to exert appreciable renoprotective effects [23], thus calling for the search of alternative ways to ameliorate CIN. In a number of studies, augmentation of adenosine formation, and consequent excretion in urine evident after the CM administration, has been implicated in inducing sustained vasoconstriction of afferent arterioles and vasodilation of efferent arterioles, thus reducing renal glomerular filtration rate and developing renal ischemia [24,25,26,27]. Studies involving theophylline, a direct selective renal adenosine antagonist, demonstrated controversial results with respect to the renoprotective vasodilatory properties of the latter [25,26,27].…”
Section: Discussionmentioning
confidence: 99%